Assessing the efficiency of an innovative plastics inventory tool in reduction of single-use plastics (SUP) consumed within the households of Bergedorf Municipality, Germany - Emma Magdalena Kloodt (2024)
Introduction: The creation of plastic was aimed at making life more comfortable. While recyclable plastic remains in a reusable cycle, single-use plastics (SUPs) is disposed of after a single use. The resulting plastic waste is becoming an increasing global environmental problem. In addition to legal regulations, there are alternative methods of solving this problem with growing SUP waste. This paper investigates the effectiveness of a Plastics Inventory Tool for private households. Materials and methods: For a better understanding of the current situation, a literature review was done to assess the composition and decomposition of plastic, as well as the relevance and burdens of plastics and the current legal regulations. Search engines such as PubMed, Google Scholar and ResearchGate were used to identify comparable studies, articles and other scientific research. Two questionnaires and the plastic inventory tool were used to collect the data. The results were mainly analysed statistically. The correlations between numerous variables of the questionnaires and the tool were compared.